Investigation of heat and mass transfer characteristics during the flame propagation of biomass straw from an initial linear fire source. (15th February 2023) - Li, Cong; Xu, Zixuan; Wang, Yuqing; Xu, Wenbo; Yang, Rui; Zhang, Hui
Abstract: Biomass straw has gradually received attention as a new energy that is easily accessible. The deep understanding of burning characteristics is critical to the efficient and safe utilization of biomass straw as a new energy, and further benefit to estimate the hazard of straw fire disasters. In the present study, the straw stacked into a rectangle with a length of 1 m, and widths from 0.1 m to 0.6 m was ignited from in a width with a linear-source fire. The heat and mass transfer characteristics during the flame propagation were investigated. The results showed that the flame front shape evolved from concave to convex as the straw width widened. Specifically, the critical transition range of straw width was from 0.3 m to 0.4 m due to the change of the dominant heat transfer factors. The residual mass of straw decreased linearly because of the uniform flame spreading process, indicating a constant MLR. The MLR was determined by the function of the aspect ratio of the instantaneous combustion area, which is shown as n + 1 / n . The flame temperature above the center position of the rectangular straw increased first and then dropped gradually. The peak dimensionless temperature presented a piecewise function with ( z − z 0 ) m ˙ − 2 / 5 . Highlights: Combustion characteristics and flame propagation of biomass straw were investigated. Shape of flame front evolved from concavity to convexity as the straw width widened. Flame front spread forward at a constant speed proportional to the straw width. Mass loss rate (MLR) was determined by the function of aspect ratio of combustion area. Dimensionless flame temperature presented a piecewise function with vertical height.